AMPK activators for the prevention and treatment of neurodegenerative diseases. (3rd October 2021) - Neumann, Natalie R.; Thompson, David C.; Vasiliou, Vasilis
ABSTRACT: Introduction: As the global population ages at an unprecedented rate, the burden of neurodegenerative diseases is expected to grow. Given the profound impact illness like dementia exert on individuals and society writ large, researchers, physicians, and scientific organizations have called for increased investigation into their treatment and prevention. Both metformin and aspirin have been associated with improved cognitive outcomes. These agents are related in their ability to stimulate AMP kinase (AMPK). Momordica charantia, another AMPK activator, is a component of traditional medicines and a novel agent for the treatment of cancer. It is also being evaluated as a nootropic agent. Areas covered: This article is a comprehensive review which examines the role of AMPK activation in neuroprotection and the role that AMPK activators may have in the management of dementia and cognitive impairment. It evaluates the interaction of metformin, aspirin, and Momordica charantia, with AMPK, and reviews the literature characterizing these agents' impact on neurodegeneration. Expert opinion: We suggest that AMPK activators should be considered for the treatment and prevention of neurodegenerative diseases. We identify multiple areas of future investigation which may have a profound impact on patients worldwide.